Neoadjuvant Targeted Therapies for Non-Small Cell Lung Cancer from the Surgical Perspective - Bulut, Halil İbrahim and Turna, Akif (Cerrahpaşa Medical Journal, 2023)
Non-small cell lung cancer is the main type of lung cancer which is the broadest and deadliest cancer worldwide. Despite improvements in treatment approaches and diagnosis programs, the expected survival rate for non-small cell lung cancer has still not been reached. The heterogeneous and case-based nature of non-small cell lung cancer plays a role in lower-than-expected success rates. Neoadjuvant treatment approaches are suggested to increase the success of surgical treatment. However, conventional neoadjuvant strategies cannot provide the expected success rate due to the heterogeneous and complicated molecular pathogenesis of non-small cell lung cancer. Case-based treatment settings are required to overcome these features of non-small cell lung cancer and achieve a better outcome in treatment. In this review, the feasibility and oncological benefits of using neoadjuvant targeted therapies, which have developed in recent years and provide case-based treatment approaches, are discussed from the perspective of the surgeon. Cite this article as: Bulut Hİ, Turna A. Neoadjuvant targeted therapies for non-small cell lung cancer from the surgical perspective. Cerrahpaşa Med J. 2023;47(1):1-6.